The Involvement of Mycobacterium Type III-A CRISPR-Cas System in Oxidative Stress - Yang, Fan; Xu, Lingqing; Liang, Lujie; Liang, Wanfei; Li, Jiachen; Lin, Daixi; Dai, Min; Zhou, Dianrong; Li, Yaxin; Chen, Yong; Zhao, Hui; Tian, Guo-bao; et al. (Frontiers in Microbiology, 2021)
Type I and type II CRISPR-Cas systems were employed to evade host immunity by targeting interference of bacteria’s own genes. Although Mycobacterium tuberculosis (M. tuberculosis), the causative agent of tuberculosis, possesses integrated type III-A CRISPR-Cas system, its role in mycobacteria remains obscure. Here, we observed that seven cas genes (csm2~6, cas10, cas6) were upregulated in Mycobacterium bovis BCG under oxidative stress treatment. Deletion of TCR (Total CRISPR system) results in increased sensitivity in response to H2O2 and reduced cell envelope integrity. By using RNA-Seq, 590 differential expression genes were found in mutant for TCR, of which 220 genes were upregulated and 370 genes were downregulated, indicating an important role of TCR in controlling gene expression in mycobacteria. Moreover, knockdown of TCR-regulated genes with CRISPR interference displayed a reduced survivability upon oxidative stress. Consistently, disrupting TCR led to poor intracellular survival in vivo and in vitro. In addition, we showed for the first time that TCR contributed to the regulation of regulatory T cell population, supporting a role of TCR in modulating host immunity. These observations demonstrate that type III-A CRISPR-Cas system as an important factor for intracellular survival and host immunoregulation in mycobacteria, thus may be a potential target for therapy.